Convergence of PPTCT with RCH Services in a District Hospital, Haryana - Bhagat, Puneet; Tiwari, Vijay Kumar; Raj, Sherin; Nair, Kesavan Sreekantan; Piang, Lam Khan (Indian Journal of Community Health, 2014)
Background: The integration of PPTCT and RCH activities is an important strategy for universal screening of ANC mothers through available government health infrastructure in a district. The objective of this study was to understand process and analyzing outcome of convergence of PPTCT & RCH services in a District Hospital. Methods: The study was a descriptive study conducted in district hospital, Gurgaon. Results: In the district hospital Gurgaon percentage of women counseled at ICTC has increased from 77% to 89.4% and percentage of women tested has increased from 75% to 87.8% during 2010 and 2011. However, not all women tested positive delivered at hospital. Only 6.7% women were knowing about transmission of HIV from mother to baby. About 60% ANC registration are delayed primarily due to lack of family support (71%). Majority of ANC women got HIV screening at district hospital due to non-availability of facility at CHC/PHC levels. About 58% of Institutional deliveries in the State are in private hospitals, but they still need to be involved in PPTCT. Conclusion: Currently, convergence of PPTCT and RCH services seems to be fragmented and at initial stage. Convergence need to be taken up at policy, planning, implementation, capacity building, resource mobilization and monitoring for success of the initiative in the state.